Greater trochanteric osteotomy and subtrochanteric osteotomy in primary/revision total hip arthroplasty - Pan, Yuqi; Chen, Yunsu (Frontiers in Surgery, 2023)
Osteotomy of the femur is necessary in some cases of primary/revision total hip arthroplasty (THA) procedure. There are two mainly used femur osteotomy methods in THA: greater trochanteric osteotomy and subtrochanteric osteotomy. Greater trochanteric osteotomy can improve hip exposure, provide greater stability against dislocation and favorably influence the abductor moment arm. Whether in the primary or revision THA, greater trochanteric osteotomy has its unique position. Subtrochanteric osteotomy adjusts the degree of femoral de-rotation and corrects the leg length. It is widely used in hip preservation and arthroplasty surgery. All osteotomy methods have specific indications, while nonunion is the commonest complication. In this paper, we analyze the greater trochanteric osteotomy and the subtrochanteric osteotomy in primary/revision THA and summarize the characteristics of different osteotomy methods.